EatxCali Keynote speaker: Carlos Monteiro, Professor at the School of Public Health, University of São Paulo, Brazil. Brazil’s dietary guidelines: A model for the region? - International Center for Tropical Agriculture (2015)
Keynote speaker: Carlos Monteiro, Professor at the School of Public Health, University of São Paulo, Brazil. EATxCali brings together representatives from academic and government institutions, international agencies, businesses, and civil society to rebuild food systems, and ensure that consumers have access to healthy and more sustainably produced food.